IDENTIFICATION OF VIBRIO CHOLERAE, VIBRIO PARAHAEMOLYTICUS, AND VIBRIO VULNIFICUS BACTERIA IN BATIK SHELLS (PAPHIA UNDULATA) CAUGHT AT PENGAMBENGAN BEACH, JEMBRANA REGENCY - Maharani, Ida Ayu Komang Ananta; Pinatih, Komang Januartha Putra; Darwinata, Agus Eka; Tarini, Ni Made Adi (Universitas Udayana, 2024)
Indonesia is a maritime country with vast seas and beaches equipped with natural riches stored in them. Global warming causes several changes in the ocean, including the increase in bacteria commonly found in the ocean, such as Vibrio sp. bacteria which can infect various animals in the ocean. Several species of bacteria Vibrio sp. that can infect humans are Vibrio cholerae, Vibrio parahaemolyticus and Vibrio vulnificus which can cause significant complaints in the human digestive tract, wound infections, and even sepsis. This research aims to determine the bacterial contamination of Vibrio cholerae, Vibrio parahaemolyticus, and Vibrio vulnificus in batik shell (Paphia undulata) caught at Pengambengan Beach, Jembrana Regency. This research is a quantitative observational study with a cross sectional research approach and uses convenience sampling as a sampling technique. Based on several research stages starting from cultivating bacteria in APW liquid media to conducting tests on TSIA media, the results showed that from 70 samples, 16 samples were found to be positive for Vibrio sp. consisting of 11 positive samples for Vibrio vulnificus and five positive samples for Vibrio parahaemolyticus. The results of this study showed that 16 positive samples of Vibrio sp. bacteria were found from batik shell (Paphia undulata) caught at Pengambengan Beach, Jembrana Regency. Keywords: Vibrio cholerae, Vibrio parahaemolyticus, Vibrio vulnificus